Evaluation of Customers’ Expectations and Perceptions of Service Quality Dimensions: A Study of South African Post Office in the North-West Province - Eposi, Elsie Mbua (International Review of Management and Marketing, 2023)
The study seeks to measure customers' expectations of service quality provided by managers and frontline employees against their perceptions of service quality in Post offices in the North-West Province of South Africa and to determine the gap between customers ‘expectations and their perceptions of service quality using the five service quality dimensions. Data were collected by SERVQUAL questionnaire to examine the areas of tangibility, reliability and responsiveness, assurance, and empathy from 384 post office customers. To select respondents for this study, non-probability sampling techniques were used, mostly convenient approaches. Using factor analysis, five characteristics of service quality were identified: tangibility, reliability and responsiveness, assurance, and empathy. According to the study's findings, A negative gap was observed in consumer expectations and perceptions of the quality of postal services delivered to consumers. This means that the quality of services delivered to postal consumers in the five-post offices was less than what they expected. The highest gap was related to tangibles and assurance. Therefore, it is mandatory for management to focus on tangibles and assurance in order to improve postal services. The study argues that managers should strive to improve the frontline employee’s willingness to help, respond quickly to queries, competence in providing efficient services, making customers feel secure when receiving services, schedule appointments on time, having customers' best interests at heart, and be of good behaviour. These qualities instils confidence in customers. These qualities that need to be renewed are categories under the post office's reliability, tangibility, responsiveness, and assurance characteristics.